Development and application of primers for the class Dehalococcoidia (phylum Chloroflexi) enables deep insights into diversity and stratification of subgroups in the marine subsurface. (26th June 2014) - Wasmund, Kenneth; Algora, Camelia; Müller, Josefine; Krüger, Martin; Lloyd, Karen G.; Reinhardt, Richard; Adrian, Lorenz
Summary: Bacteria of the class D ehalococcoidia (DEH) (phylum C hloroflexi ) are widely distributed in the marine subsurface and are especially prevalent in deep marine sediments. Nevertheless, little is known about the specific distributions of DEH subgroups at different sites and depths. This study therefore specifically examined the distributions of DEH through depths of various marine sediment cores by quantitative PCR and pyrosequencing using newly designed DEH 16S rRNA gene targeting primers. Quantification of DEH showed populations may establish in shallow sediments (i.e. upper centimetres), although as low relative proportions of total Bacteria, yet often became more prevalent in deeper sediments. Pyrosequencing revealed pronounced diversity co‐exists within single biogeochemical zones, and that clear and sometimes abrupt shifts in relative proportions of DEH subgroups occur with depth. These shifts indicate varying metabolic properties exist among DEH subgroups. The distributional changes in DEH subgroups with depth may be related to a combination of biogeochemical factors including the availability of electron acceptors such as sulfate, the composition of organic matter and depositional regimes. Collectively, the results suggest DEH exhibit wider metabolic and genomic diversity than previously recognized, and this contributes to their widespread occurrence in the marine subsurface.